Análise da eficiência de métodos de controle de Enchentes na atenuação de picos de cheias utilizando o modelo computacional SWMM Storm Water managemente model - SILVA, Karla Alcione da (2007)
This research presents an evaluation of the eficiency of four flood control measures applied to an urban basin in the city of Goiânia, State of Goiás, Brazil. Goiânia shows frequent flooding problems. The following factors have been identified as causes of the floodings: (1) significant number of impervious areas (2) lack of green areas, (3) insuficient capacity of the pipe network to convey the produced water volume. Small detention basins, infiltration trenches and the increase of permeable areas (30-50%) within parcels have been evaluated as flood control measures as well as the use of the Lago do Bosque dos Buritis as a detention basin. For this purpose, the Stormwater Management Model SWMM has been applied for evaluating 11 hypothetic management measures in the water basin. The later control measures were evaluated individually as combined. In determining the impervious area index of the studied area, field visits have been carried out, which showed high imperviousness. (86.16%). A synthetic rainfall time series, derived from the equation proposed by Costa e Brito (1999) with recurrence of 2 years, has been used in the simulations. Horton`s equation was applied to represent infiltration with parameters presented in Moura (2005). The scenario which combines the use of infiltration trenches and the increase of pervious areas to 50% has shown to be the best solution in reducing peak flow with 43% eficiency. On the other hand, the scenario using detention basins presented the smallest efficiency (3%).